UPAYA PENINGKATAN KESEHATAN MENTAL MELALUI MANAJEMEN PENDIDIKAN KARAKTER BERBASIS ETIKA PADA ANAK USIA PRASEKOLAH - Bingar Hernowo; Filu Marwati Santoso Putri (LPPM STIKES Madani Yogyakarta, 2019)
The busy parents and the mistake of actualizing one's wealth by introducing children to gadgets earlier can make the child's experience mental illness. Parents feel that the task of educating children is enough to put children in a school and pay for all the children's needs. PAUD Pelangi Anak Bangsa is a pre-school education where almost all children know and are really close to gadgets and it has an impact on their mental condition which they were more easily irritable, sulky and difficult to control. The purpose of this community service activity is to hold health education in the PAUD Pelangi Bangsa environment to provide knowledge about the management of ethics-based character education as an effort to improve the mental health of pre-school children. The output in this community service activity is to increase knowledge about the management of ethics-based character education as an effort to improve mental health of pre-school children, community service reports and to become an output for scientific articles in Abdimas Madani National Journal Volume 1 No 1 Year 2019. The community involved in this society education were mothers of children in Pelangi Bangsa ECD pre-school. Lectures was used as the method and followed by focus group discussion. The result of the activity is that the mothers of pre-school children at PAUD Pelangi Bangsa were very enthusiastic in participating in the activity and began to understand the management of ethics-based character education to improve children's mental health.